ANALISIS PUTUSAN PENGADILAN NEGERI CIBINONG NOMOR 33/PDT.G/2019/PN.CBI DIMANA PENGGUGAT TIDAK MEMILIKI KEWENANGAN HUKUM ATAS DIBATALKANNYA SERTIFIKAT OLEH PTUN (STUDI KASUS NOMOR 158/G/2015/PTUN-BDG) - Bred Klenten; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
The emergence of legal disputes stems from objections related to claims for land rights both onland status, priority and ownership. The problems is what is the consideration of the CibinongDistrict Court judge who grants PT. Sentul City which has no legal authority as a plaintif with thecancellation of SHGB No. 305/Desa Karang Tengah and how the legality of land ownership iscivil but the proof of ownership is cancelled. The research method is a normative juridical. Theresults showed that the things that were considered by the Cibinong District Court Judge whogranted PT. Sentul City which has no legal authority as a plaintif with the cancellation of SHGBNo. 305/Desa Karang Tengah is the transfer of land rights made by the Plaintif to the land owneras referred to in the 9 SPH that has been carried out legally. Cancellation of the certificatethrough the Administrative Court does not only immediately erase the civil rights of people to theland. In relation to this case, wherein the Plaintif 's SHGB No. 305/Desa Karang Tengah has beencanceled by the Administrative Court, of course, it becomes a strong legal basis. The cancellationof the certificate by the PTUN according to the author is because there are other parties who canprove that a parcel of land that has been issued a certificate is legally and truly his property andthis is supported by a court decision that has been inkracht.